Comparison of insulin requirements across gestation in women with hyperglycemia in pregnancy: A prospective cohort study - Rao, Chong; Ping, Fan (Frontiers in Endocrinology, 2022)
Objectives The aim of this study is to explore the daily insulin dose and the percentage change in preprandial and basal insulin dosage of women with different types of hyperglycemia in pregnancy (HIP) during the whole gestation and postpartum period. Methods A total of 121 subjects with HIP requiring insulin therapy were enrolled from a prospective cohort consisted of 436 pregnant women with hyperglycemia. The subjects were divided into three groups: Group 1 [type 1 diabetes mellitus (T1DM) and maturity onset diabetes of the young (MODY)], Group 2 [type 1 diabetes mellitus (T2DM)], and Group 3 [gestation diabetes mellitus (GDM)]. The primary study measurements included daily dose and percentage of different types of exogenous insulin requirements across gestation in different groups. Results Insulin total daily dosage of Group 1 was highest among the three groups and increased significantly from the first to the second/third trimester. Percentage of preprandial insulin increased from 53.8% (46.7, 60.0) and 54.5% (42.3, 62.9) in the first trimester to 63.6% (54.9, 75.0) and 67.2% (51.8, 73.7) in the second/third trimester in Group 1 and Group 2. All subjects with T1DM and 18.6% of subjects with T2DM still required insulin administration after delivery, with a 26.9% (19.0, 46.0) and 36.7% (26.9, 52.6) decrease in total insulin dose, respectively, whereas subjects with GDM and MODY weaned off insulin completely. Conclusion The insulin requirements for pregnancy complicated with T1DM and MODY were higher than those for T2DM and GDM. In the subjects with PGDM, the insulin requirement and percentage of preprandial insulin increased gradually from early to mid- and late pregnancy.